2001
DOI: 10.1182/blood.v98.12.3441
|View full text |Cite
|
Sign up to set email alerts
|

De novo methylation of an embryonic globin gene during normal development is strand specific and spreads from the proximal transcribed region

Abstract: The recently discovered de novo methyltransferases DNMT3a and DNMT3b have been shown to be critical to embryonic development. However, at a single gene level, little is known about how the methylation pattern is established during development. The avian embryonic -globin gene promoter is completely unmethylated in 4-day-old chicken embryonic erythroid cells, where it is expressed at a high level, and completely methylated in adult erythroid cells, where it is silent. The methylation pattern of the -globin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…We propose that such repression, resulting in the observed lower transcription level of MusD compared with ETnII elements in early embryos (5) and ES cell lines (this study), stems from a higher probability of repressive chromatin and DNA methylation originating in the downstream CpG-rich retroviral region. A similar case was reported for the rho globin gene in chicken embryonic erythroid cells, in which, during normal developmental silencing, de novo methylation originates in the downstream CpG-dense region and then spreads into the promoter, silencing transcription and resulting in complete DNA methylation in adult erythroid cells (58). Notably, roughly half of the ETnII copies in the genome have methylation levels similar to MusD, but the other half are essentially unmethylated (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…We propose that such repression, resulting in the observed lower transcription level of MusD compared with ETnII elements in early embryos (5) and ES cell lines (this study), stems from a higher probability of repressive chromatin and DNA methylation originating in the downstream CpG-rich retroviral region. A similar case was reported for the rho globin gene in chicken embryonic erythroid cells, in which, during normal developmental silencing, de novo methylation originates in the downstream CpG-dense region and then spreads into the promoter, silencing transcription and resulting in complete DNA methylation in adult erythroid cells (58). Notably, roughly half of the ETnII copies in the genome have methylation levels similar to MusD, but the other half are essentially unmethylated (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…MEL cells were transfected with the -globin mini-locus that had been methylated to recapitulate the pattern of methylation observed at the endogenous gene in adult chicken RBCs. 50 After selection and dilution cloning, DNA slot blotting confirmed that the -globin mini-locus was present in MEL cells, termed MEL-cells ( Figure 6D). …”
Section: Org Frommentioning
confidence: 95%
“…The sequencing gel was dried and exposed to a phosphorimager screen (BioRad Laboratories). Methylation analysis was carried out by quantitating the intensity of C and T bands using Quantity One software (Bio-Rad Laboratories) and calculating the percentage of C/(C + T) bands, as previously described (18).…”
Section: Methodsmentioning
confidence: 99%